Thiopental Versus Propofol in Combination with Remifentanil for Successful Classic Laryngeal Mask Airway Insertion: A Prospective, Randomised, Double-Blind Trial - Akan, Mert; Cakirgoz, Mensure; Demirel, Ismail; Sarac, Omurhan; Kar, Aysun Afife; Alaygut, Ergin; Tunay, Abdurrahman (Mdpi, 2025)
Background: Remifentanil, an ultra-short-acting mu-receptor agonist, is used with propofol or thiopental for tracheal intubation without muscle relaxants. While effective with both, its combination with thiopental provides better hemodynamic stability. Thiopental has long been a standard intravenous agent for anaesthesia induction and remains a cost-effective alternative to propofol in resource-limited settings. To date, no study has directly compared the effects of thiopental-remifentanil and propofol-remifentanil combinations on LMA insertion conditions. This study aims to compare the effects of thiopental or propofol with 2 mu g center dot kg(-1) remifentanil on laryngeal mask airway (LMA) insertion conditions and success in a prospective, randomised double-blind study. Method: The study included 80 premedicated ASA I-II patients, aged 18-65, randomised into Group P (propofol) and Group T (thiopental). Anaesthesia induction was with 2 mu g center dot kg(-1) remifentanil, followed by 5 mg center dot kg(-1) thiopental or 2.5 mg center dot kg(-1) propofol. LMA insertion occurred 90 s post-induction. LMA insertion conditions were evaluated using a six-variable scale. Systolic arterial pressure (SAP), diastolic arterial pressure (DAP), mean arterial pressure (MAP), heart rate (HR), and bispectral index monitor (BIS) values were recorded at baseline, 1 min pre-insertion, and at 1, 2, 3, 4, and 5 min after insertion. Apnoea duration, loss of eyelash reflex duration, insertion duration, number of attempts, and perioperative complications were also documented. Results: Demographic data were similar. Group P showed significantly shorter eyelash reflex loss and LMA insertion durations, longer apnoea duration, and higher rates of full mouth opening, excellent LMA insertion condition, and hypotension or bradycardia compared to Group T (p < 0.05). Group P had significantly lower HR, SAP, DAP, and MAP at various time points (p < 0.05). There were no significant differences in blood presence on LMA, sore throat, or dysphagia (p > 0.05). Conclusions: In our study, administration of 2 mu g center dot kg(-1) remifentanil before induction along with thiopental or propofol was shown to provide acceptable LMA insertion conditions at comparable levels. As hemodynamic parameters were less affected, we believe the remifentanil-thiopental combination may be a suitable alternative.
Keywords: remifentanil; propofol; thiopental; laryngeal mask airway